Abertura do X Brazilian e-Science Workshop - Ocaña, Kary A. D. C. S.; Braga, Regina (Anais do Brazilian e-Science Workshop (BreSci); 2016: Anais do X Brazilian e-Science Workshop, 2016)
Mensagem da Coordenação do X Brazilian e-Science Workshop